Energy Sector Decarbonization in Vietnam : Background Note to the Country Climate and Development Report (CCDR) - World Bank (Washington, DC, 2022)
Vietnam has made remarkable economic progress over the past 30 years; however, growth was supported by increasing reliance on coal-based energy. The energy sector would continue the expansion of coal-based energy with the significant increase in the installed capacity of coal power plants under previous plans. Vietnam has committed to achieving net-zero emissions by 2050 and gradually phasing out the use of coal for power generation. Selecting lower carbon pathways for the future growth of the energy sector requires the study of interdependencies of the power system through a robust analytical approach. The choice of decarbonization scenario should be based on a careful review of implications and opportunities at the sector level as well as more broadly at the level of the economy. Energy sector decarbonization would require the development of ‘just transition’ oriented policies and regulations to support the people, communities, and businesses. World Bank Group stands ready to provide comprehensive support for designing and implementing a low-carbon future for the energy sector.